Mayer-Rokitansky-Kuster-Hauser Type I Syndrome - A Case Report - BB, Sharma; S, Sharma; Y, Singh; J, Balesa (Indian Journal of Case Reports, 2015)
Mayer-Rokitansky-Kuster-Hauser (MRKH) Syndrome is not uncommon as this is a part of the Mullerian agenesis. This isusually diagnosed during adolescent period when signs and symptoms of the ongoing changes in female body type are delayed. We present 17 years old adolescent female who presented with primary amenorrhoea as the normal menstruation did not start at puberty. She was diagnosed as MRKH Type I Syndrome on the basis of radiological investigations.